2019
DOI: 10.1080/00927872.2018.1476522
|View full text |Cite
|
Sign up to set email alerts
|

Power graphs of (non)orientable genus two

Abstract: Let G be a finite non-cyclic group. The non-cyclic graph Γ G of G is the graph whose vertex set is G \ Cyc(G), two distinct vertices being adjacent if they do not generate a cyclic subgroup, where Cyc(G) = {a ∈ G : a, b is cyclic for each b ∈ G}. In this paper, we classify all finite non-cyclic groups G such that Γ G has (non)orientable genus one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Further, Doostabadi et al [11], characterized the finite groups whose power graphs are of (non)orientable genus one. Then all the finite groups with (non)orientable genus two power graphs have been characterized in [28]. The undirected power graphs of groups have been studied in other aspects, see [7,9,13,24,26] and references therein.…”
Section: Historical Background and Main Resultsmentioning
confidence: 99%
“…Further, Doostabadi et al [11], characterized the finite groups whose power graphs are of (non)orientable genus one. Then all the finite groups with (non)orientable genus two power graphs have been characterized in [28]. The undirected power graphs of groups have been studied in other aspects, see [7,9,13,24,26] and references therein.…”
Section: Historical Background and Main Resultsmentioning
confidence: 99%
“…The concepts of power graph and undirected power graph were first introduced by Kelarev and Quinn [18] and Chakrabarty et al [6], respectively. In recent years, the study of power graphs has been growing, see, for example, [4,5,21,22]. Also, see [1] for a survey of results and open problems on power graphs.…”
Section: Introductionmentioning
confidence: 99%
“…This article only considers the undirected power graphs corresponding to finite groups. Later on, in [2,3] it was shown that the power graph of two finite groups G and H with the same order, are isomorphic if and only if given any d | |G|, the number of elements of G of order d is equal to the number of elements of H of order d. The strong metric dimension of the power graph of a finite group is studied in [9] and the power graphs which are non-orientable and genus two are studied in [8]. For a detailed survey on the power graphs and related areas, see the survey articles [1], and [6].…”
Section: Introductionmentioning
confidence: 99%